2014
DOI: 10.1371/journal.pone.0098913
|View full text |Cite
|
Sign up to set email alerts
|

A Defective TLR4 Signaling for IFN-β Expression Is Responsible for the Innately Lower Ability of BALB/c Macrophages to Produce NO in Response to LPS as Compared to C57BL/6

Abstract: C57BL/6 mice macrophages innately produce higher levels of NO than BALB/c cells when stimulated with LPS. Here, we investigated the molecular events that account for this intrinsic differential production of NO. We found that the lower production of NO in BALB/c is not due to a subtraction of L-arginine by arginase, and correlates with a lower iNOS accumulation, which is independent of its degradation rate. Instead, the lower accumulation of iNOS is due to the lower levels of iNOS mRNA, previously shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We examined whether WK2-16 affected NF-κB, STATs, and MAPK signaling pathways, which regulate iNOS and COX-2 expression at the transcriptional level, to further clarify the underlying mechanisms. A previous study demonstrated that sufficient activation of STAT-1 was necessary for the full transcription of iNOS in macrophages, whereas NF-κB was activated [41]. STAT-1 and STAT-3 binding sites are widely located in the microglial genome, and manipulation of the constitutive expression of STAT-1 and STAT-3 mimics LPS stimulation, inducing the transcription of hundreds of genes and results in inflammatory cytokines production in microglia [42].…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether WK2-16 affected NF-κB, STATs, and MAPK signaling pathways, which regulate iNOS and COX-2 expression at the transcriptional level, to further clarify the underlying mechanisms. A previous study demonstrated that sufficient activation of STAT-1 was necessary for the full transcription of iNOS in macrophages, whereas NF-κB was activated [41]. STAT-1 and STAT-3 binding sites are widely located in the microglial genome, and manipulation of the constitutive expression of STAT-1 and STAT-3 mimics LPS stimulation, inducing the transcription of hundreds of genes and results in inflammatory cytokines production in microglia [42].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate this methodology, we used mice with lipopolysaccharide- (LPS-) induced endotoxemia, as this model is well characterized by an inflammatory reaction with an NADPH-oxidase-dependent oxidant burst and elevation in RNS through the inducible nitric oxide synthase (NOS-2) pathway [17]. The LPS insult is known to increase the level of proinflammatory cytokines [18, 19], which leads to excessive production of nitric oxide ( ∙ NO) via NOS-2 and increased production of prostanoids due to cyclooxygenase-2 (COX-2) induction as well as concomitant alternative mechanisms leading to endotoxemic multiorgan failure [20]. Since little is known regarding tissue-specific differences in changes of ROS/RNS balance in vivo as most studies focused on a single target organ or analysis of proinflammatory cytokines [19, 20], the tissue- and time-dependent changes in DHE oxidation products were supplemented by ex vivo detection of ∙ NO production using EPR spin trapping in the isolated aorta, lung, and liver tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes Mellitus is a multifactorial metabolic disease associated with various conditions, including genetic predisposition, physical inactivity and mainly obesity. In fact, obesity is the second most important risk factor for various diseases [1] and its association with diabetes is very well established [2, 3]. As in the rest of the world, obesity has attracted attention in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between BAI and other adiposity indexes have been also explored [6, 7]. However, according to Alvim et al [2], ethnic differences may influence the discriminatory power of BAI, as well as several other anthropometric indices, in assessing the risk of T2DM. In agreement with this reality, our main interest is to investigate the influence of BAI on T2DM in a sample of the Brazilian population, after 5-year follow-up.…”
Section: Introductionmentioning
confidence: 99%